ASPECTUAL RELEVANT CLASSES AND SPECIFIC ASPECTS FUNCTIONS OF THE VERB: THE PROBLEM OF RELATIONSHIP - Калько, Микола (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The article deals with the problem of specific-aspect functions as a manifestation of the interaction of the aspects of aspect with the internal (aspectual relevant classes of verbs) and external (aspects of weighty syntaxes, grammatical and functionally-grammatical categories, with which the species interacts, tokens – function markers, aspect of syntactic constructs) context .The chief approach to the description of aspectuality regarded by Lyons as objectivist had been created by Maslov and Wendler in the mid 20th century being later established by the aspectuality studies of the late 20th - early 21st century, in the so called «binary» aspect theory. It proves the necessity of applying aspectual analysis for the whole number of meanings and all contexts of the verb since aspectual classes 12 (lexical component of aspectuality) and the category of aspect (grammatical component of aspectuality) are not aimed at a verbal lexeme in general but at each lexical-semantic variant of the lexeme. Ignoring this factor, in our opinion, results in cute polemics over numerous aspectual issues which originated through the attempts to force the aspect into rigid category framework, beyond the influence of various triggers on the aspectual significance of the verb. Рurpose. Since in the linguistic theory the mentioned problem is outlined only in general terms, there is a need for a more linguistic study of the mechanism of the interaction of the system and the environment in the realm of the category of the aspect of the Ukrainian verb, and the establishment of the repertoire of concretespecific functions as semantic spectra of the executed and inappropriate species. The interaction of specificaspect functions with the essentially relevant classes is the goal of this gender. Methods. Integrated аspect diagnostics as integration methodology, which involves the purposeful use of logical, component, word-forming, oppositional and distributive analysis, selection of the corps of fragments discourse. Results. The study of functional spectrum of species forms makes it possible to distinguish between eighteen specific-type functions of the inadequate and six functions of the finished species. The wider range of imperfect forms is based on the fact that imperfectivs can denote both the process and the event, and the perfectivs of the same – only an event. Originality. Concrete-aspect functions suggest a close interaction of the semantics of the semantics of the context: the intracellular (aspectual relevant classes of verbs: terminatives, activatives, sentencives, etventives, relatives) and extrinsic ones, which are: 1) grammatical categories, in particular time, mode and transitive vs intransitive; functional-grammatical categories: modality, quantitative, negation; 2) aspectally relevant syntaxes, in particular temporal and quantitative; 3) lexemes-markers of a certain function, such as: here, see, notice; 4) the aspect of syntactic construction. Conclusion. Aspectual studies being generally orientated in an objectivist way, together with the immediate consideration of the aspect influencing the grammatically specified lexical phenomena, like the aspectual regarded verbal classes, are new to the Ukrainian lingual studies, though quite natural in the process of investigating formal grammatical and functioning grammatical traits of the Ukrainian verbal aspect. Analysis the aspect associated with the discovery of a specific specificity of the species behavior of the verbs in view of various factors of influence: paradigmatics, syntagmatics, pragmatics.